1992
DOI: 10.1111/j.1600-0404.1992.tb05487.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous thoracolumbar spinal cord infarction: report of six cases

Abstract: We present a retrospective study of 6 patients with spinal cord infarction in the territory of the Adamkiewicz artery. In all patients, the clinical picture was stereotyped: sudden onset of paraplegia and bilateral radicular pain, dissociated sensory loss below the level of infarction and sphincter dysfunction. Emergency neuroradiological investigation ruled out a compressive lesion in all cases. In one patient, spinal angiography was performed and identified an occlusion of the Adamkiewicz artery. Treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 11 publications
3
13
1
Order By: Relevance
“…Previous studies observed a more favorable outcome in ischemic myelopathy of cryptogenic origin. 15,16 However, the origin had no predictive value in our series.…”
Section: Discussioncontrasting
confidence: 42%
“…Previous studies observed a more favorable outcome in ischemic myelopathy of cryptogenic origin. 15,16 However, the origin had no predictive value in our series.…”
Section: Discussioncontrasting
confidence: 42%
“…The typical presentation of FCE, as exemplified by our case, often includes sudden onset of localized back pain associated with a suggestive story and mechanism. In thrombotic infarction, sudden pain is often absent and, if present, may have more of a radicular or girdle distribution (1,(8)(9)(10). In addition, the characteristic neurologic indicators of FCE often include a symptom-free interval and a progression in time that is not characteristic of a patient with a thrombotic infarction, many of whom often have numbness and weakness at onset (1,(8)(9)(10).…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism was thought to result from nerve root ischemia [19]. Neck pain that radiated to the shoulder or upper limbs was often seen in cervical hemicord infarction [20].…”
Section: Discussionmentioning
confidence: 99%